Economics of social issues - Sharp, Ansel M. (McGraw-Hill/Irvin, 2002)
Designed as an introduction to general economics for non-majors, Sharp/Register/Grimes' text presents economic concepts as useful tools to analyze contemporary social issues. The book may also be used to supplement principles courses. The Economics of Social Issues has garnered a loyal user following for its timely and impartial handling of current social issues which dominate newspapers and television news. While the issues are contemporary and the supporting information updated, the authors remain objective.